Randomized controlled trial of the efficacy of attention and emotional regulation training for children with attention deficit hyperactivity disorder - YANG Letian, HONG Danping, DANG Caiping, ZHU Zhihang, HU Yingzi, PENG Kaiqi, XU Yixuan, LIU Jinlan, YANG Chanjuan, CHENG Daomeng, YU Meng, YIN Weizhen (Xin yixue)
Objective To examine the intervention effects of attention and emotional regulation training on children with attention deficit hyperactivity disorder （ADHD）. Methods A total of 59 children with ADHD were recruited for group intervention in this randomized controlled double-blind trial. At the beginning and end of the intervention， two interviews were delivered for parents and six sessions of group intervention for children. All children were divided into the intervention groups with attention training （attention group） and emotional regulation training（emotional group） as the objectives， and contorl group. The SNAP-Ⅳ scale was used to assess ADHD symptoms before and after the intervention. Emotionality and Emotion Regulation Scale and other scales were used to measure emotional response and emotional regulation ability. The Matson Evaluation of Social Skills with Youngsters scale was used to measure social skills. Results The scores for ADHD were decreased significantly in all three groups （all P < 0.05）. However， only two intervention groups showed a significant reduction in oppositional defiant disorder scores （both P < 0.05）. In terms of emotionality and emotional regulation， all three groups exhibited significant reductions in emotional reactivity scores （all P < 0.001） and scores for negative or unstable emotions （all P < 0.05）. However， only the emotional intervention and control groups demonstrated statistically significant improvements in emotional regulation ability （all P < 0.05）. For social skills， all three groups showed a significant decrease in self-centeredness scores （all P < 0.05）. Conclusions Both attention training and emotional regulation training intervention regimens effectively mitigate ADHD symptoms， improve emotional regulation ability， and social skills in children with ADHD. In the active control group， ADHD symptoms can be alleviated to certain extent， but it is insufficient in improving oppositional defiance. In the the emotional intervention and active control groups， a more significant impact on improving emotional dysregulation can be obtained than that in the attention intervention group.